The Implication of Al-Qur'an Education Park (TPQ) on Increasing the Religious Values of Children in Sukolilan Village, Patebon District, Kendal Regency - Nur Maulina Maftukhah; Isma Sari; Rizma Aviana; Anzil Maulana Sifa’; Nabila Nilta Syarof; Muhammad Syarif Hidayat (Universitas Palangka Raya, 2024)
Religious education is the basic education that children need and has a direct impact on children's behavior and development. Religious education in children is the beginning of identity formation. Children who receive information about the Quran from a young age will grow up to be good and religious people. Learning to read and write the Quran as a foundation for learning the Quran from an early age will create good habits and instill a sense of love in children, their hearts and minds. This research uses field studies with descriptive qualitative methods with data collection techniques in the form of direct observation in the field. The results of this study indicate that the Al-Qur'an Education Park (TPQ) has implications for increasing the Religious Values of Children